EDUKASI AKUNTANSI DAN PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN UMKM KONVEKSI “UNIFORM MANUFACTURING DAN SERBA-SERBI OLSHOP” - Baiq Anggun Hilendri Lestari; Lalu Takdir Jumaidi; Iman Waskito (Jurnal Abdimas Sangkabira, 2022)
The Micro Small Medium Enterprise (MSME) sector has proven to be resilient when there is an economic crisis at this time, only the MSME sector has survived the economic collapse during the Covid-19 pandemic while the larger sector has actually collapsed due to the crisis. Capital is an important factor for developing a business and to get capital loans from financial institutions, financial statements are very important because through these financial statements, banks and financial institutions can assess the ability to pay loans from these MSMEs. In this regard, one of the contributions of academics is to carry out community service. The purpose of this activity is to provide accounting education and assistance in the preparation of financial statements to MSMEs "Uniform Manufacturing & Serba Serbi Ollshop". This MSME is located in Selagik village, Terara district, East Lombok regency and its business activities are in the convection sector. Based on the results of community service, it can be concluded that the owner of the convection MSME "Uniform Manufacturing and Sundry Olshop Selagik village, Terara District, East Lombok, do not know about the preparation of financial statements. Therefore, there needs to be improvements in business financial management by compiling financial statements in accordance with applicable accounting standards.